Chitosan nanoparticles: process and their application as drug delivery. - Hari Eko Irianto; Ijah Muljanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2011)
Chitosan has wide ranges of potential applications and Indonesia possesses abundant rawmaterial sources such as crab and shrimp shells to produce it. Chitosan have beneficial properties,i.e. biocompatible, biodegradable, non-toxic and inexpensive. Nowadays, several experimentson the preparation of chitosan into nanoparticles and its utilization as drug delivery for varioustargeted therapies have been conducted. Chitosan nanoparticles can be prepared using variousmethods, e.g. emulsion cross-linking, precipitation, spray drying, emulsion-droplet coalescencemethod, ionic gelation, reverse micellar method and polyelectrolyte complex. Applications ofchitosan nanoparticles as drug delivery can be performed through diverse administrations includingparenteral, peroral and ocular, non-viral gene delivery vectors, vaccine delivery, and photodynamictherapy.